Selected Aspects of the Mental Functioning of Women After Childbirth in a Hospital During a Pandemic - Kułak-Bejda, Agnieszka; Malinowska-Gleń, Maryla; Bejda, Grzegorz; Slifirczyk, Anna; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2022)
Introduction: The COVID-19 pandemic is stressful for pregnant women, their families, and their unborn baby. Aim of the study: The study aimed to assess the impact of a pandemic on the mental state of women after childbirth. Material and methods: The study included 363 women hospitalized after delivery. The study used a diagnostic survey method using the proprietary questionnaire and the Familly Affluence Scale (FAS), Edinburgh Postnatal Depression Scale (EPDS), Jong Gierveld Lone-liness Scale (DJGLS), The Basic Hope Inventory (BHI -12), and General Self Efficacy Scale (GSES) Results: Suspicion of postpartum depression was found in 109 women (mean: 15.28 ± 2.22) - group I, and no suspicion of it in 254 subjects (mean: 6.03 ± 2.63) - group II. Mean values of the sense of loneliness in group I (27.11 ± 6.00) were higher than in group II (21.35 ± 7.02), and the basic hope - BHI - 12, in group I - lower (27.92 ± 5.14) than in group II (31.75 ± 4.97). In the Generalized Own Efficacy Scale, the group I obtained lower mean values (28.07 ± 4.86 points and 5.87 ± 1.96 points) than group II (30.97 ± 3.77 points and 6.02 ± 1 points), 38 sten). Conclusions: As much as 30% of the respondents showed a risk of postpartum depression. The most felt was the limitation of family visits during the hospital stay. In addition, the respondents were most concerned about the child's health in both groups. The feeling of loneliness in group I was higher, and basic hope and generalized self-efficacy were lower than in group II. The differences between these relationships were statistically significant.